Pengembangan Sumber Daya Pendidik Melalui Peningkatan Kualitas Pendidikan Profesi Guru Prajabatan di Indonesia - Tintingon, Josly Yakob; Usoh, Elni Jeini; Sumual, Tinneke Evie Meggy (El-Idare, 2023)
This study aims to examine the development of educator resources through improving the quality of pre-service teacher professional education in Indonesia. Literature review based on in-depth analysis of relevant sources. The results of data analysis in the field found that 3.3 million teachers, of which 1.5 million teachers were professionally certified (45%), the rest were not certified (55%), indicating that there were more teachers who were not professionally certified. research shows. In addition, Indonesia is still lacking on a national scale, around 1.4 million teachers. Of course, it is necessary to increase the number of teachers and their professionalism. This can be done with an alternative PPG Pre-service program policy. The results of the discussion in this study revealed that there was indeed an increase in the ability of post-PPG teachers compared to teachers who did not take PPG. However, this implementation needs to be carried out on an ongoing assessment and evaluation so that it runs optimally.